2015
DOI: 10.1007/s00520-015-2757-y
|View full text |Cite
|
Sign up to set email alerts
|

Financial burden of therapy in families with a child with acute lymphoblastic leukemia: report from north India

Abstract: Families spend up to seven times their monthly income over a period of 1 month on an unforeseen illness. Despite financial aid from various sources, nonmedical costs amount to nearly 2.5 times the average per capita income. Universal health insurance is the need of the hour.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 39 publications
(54 citation statements)
references
References 17 publications
2
51
0
Order By: Relevance
“…We identified 3359 articles through literature searches and included 35 articles, reporting on 29 individual studies (Figure ). Thirteen (37%) studies were conducted in Europe, 16 (46%) in North America/Australia, and six (17%) in Asia/Africa (Table ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We identified 3359 articles through literature searches and included 35 articles, reporting on 29 individual studies (Figure ). Thirteen (37%) studies were conducted in Europe, 16 (46%) in North America/Australia, and six (17%) in Asia/Africa (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…The majority of studies on income reported substantial income loss after the child's diagnosis . The proportion of parents reporting income loss and the extent of these losses varied largely.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1 Yet, the out-of-pocket health expenditures may be more catastrophic in resource-poor countries including India, where parents often have to abandon their child's cancer treatment to ensure the financial sustainability of the family. 3 Poor prognosis, prolonged travel time to treatment centers, and parents' low socioeconomic and educational status remain contributing factors to treatment abandonment. 4 The precise magnitude of costs remains largely unknown in these countries where burden of costs can be catastrophic.…”
Section: Introductionmentioning
confidence: 99%